The Effect of Adjuvant Intravitreal Dexametason to Visual Outcomes of Acute Bacterial Endophthalmitis: A Ten Years Systematic Review - Lianda, Felia; Priyanto, Tri Hendro (International Medical Journal Corp. Ltd, 2024)
Background: Endophthalmitis is a rare but potentially visually devastating condition that is defined as infection in the intraocular cavities (i.e. aqueous or vitreous humor, or both). Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Intravitreal dexamethasone does not provide additional visual benefits to endophthalmitis patients.